Effects of tannic acid on growth performance, relative organ weight, antioxidative status, and intestinal histomorphology in broilers exposed to aflatoxin B1 - Xi, Yu; Chen, Jing; Guo, Shuangshuang; Wang, Sitian; Liu, Zhipeng; Zheng, Liyun; Qi, Ya; Xu, Pengtao; Li, Lanlan; Zhang, Zhengfan; Ding, Binying (Frontiers in Veterinary Science, 2022)
A total of 480 one-day-old AA broiler chicks were randomly allocated to one of four treatments in a 2 × 2 factorial to investigate the effects of tannic acid (TA) on growth performance, relative organ weight, antioxidant capacity, and intestinal health in broilers dietary exposed to aflatoxin B1 (AFB1). Treatments were as follows: 1) CON, control diet; 2) TA, CON + 250 mg/kg TA; 3) AFB1, CON + 500 μg/kg AFB1; and 4) TA+AFB1, CON + 250 mg/kg TA + 500 μg/kg AFB1. There were 10 replicate pens with 12 broilers per replicate. Dietary AFB1 challenge increased the feed conversion ratio during days 1 to 21 (P < 0.05). The TA in the diet did not show significant effects on the growth performance of broilers during the whole experiment period (P > 0.05). The liver and kidney relative weight was increased in the AF challenge groups compared with the CON (P < 0.05). The addition of TA could alleviate the relative weight increase of liver and kidney caused by AFB1 (P < 0.05). Broilers fed the AFB1 diets had lower activity of glutathione peroxidase, catalase, total superoxide dismutase, S-transferase, and total antioxidant capacity in plasma, liver and jejunum, and greater malondialdehyde content (P < 0.05). Dietary supplemented with 250 mg/kg TA increased the activities of antioxidative enzymes, and decreased malondialdehyde content (P < 0.05). In addition, AFB1 significantly reduced the villus height and crypt depth ratio in the ileum on day 42 (P < 0.05). In conclusion, supplementation with 250 mg/kg TA could partially protect the antioxidant capacity and prevent the enlargement of liver in broilers dietary challenge with 500 μg/kg AFB1.